Computer Simulation of Gallium Arsenide Super Beta Transistors Heterostructures for High-Speed BIS - Novosyadlyi, S.P.; Huzik, V.S. (Physics and Chemistry of Solid State, 2015)
Among the semiconductor in latitude use in microelectronics for digital circuits silicon has been and remains the main material. However, today began intensively implemented circuits based on gallium arsenide. Gallium arsenide circuits of the high charge carrier mobility with a frequency range of operation of reach for chips based on silicon (Si).